2021
DOI: 10.1017/dmp.2021.27
|View full text |Cite
|
Sign up to set email alerts
|

Text4Hope: Receiving Daily Supportive Text Messages for 3 Months During the COVID-19 Pandemic Reduces Stress, Anxiety, and Depression

Abstract: Background: This study reports on the changes in stress, anxiety, and depressive symptoms of subscribers after 3 months using Text4Hope, a supportive text messaging program designed to provide support during the pandemic. Methods: Standardized self-report measures were used to evaluate perceived stress (measured with the Perceived Stress Scale-10 (PSS-10)), anxiety (measured with the General Anxiety Disorder Scale 7 (GAD-7)), and depressive symptoms (measured with the Patient Health Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 17 publications
8
62
0
1
Order By: Relevance
“…The majority of participants in this study were female (63.5%). This trend was observed in other research with similar intervention mechanisms (31,74,75). Gender plays a role as a significant determinant of mental health (76).…”
Section: Engagementsupporting
confidence: 82%
See 1 more Smart Citation
“…The majority of participants in this study were female (63.5%). This trend was observed in other research with similar intervention mechanisms (31,74,75). Gender plays a role as a significant determinant of mental health (76).…”
Section: Engagementsupporting
confidence: 82%
“…It is possible that females are more likely to subscribe to text-based support services or to complete online surveys. In the user satisfaction surveys for the Text4Mood and Text4Hope programs, over 80% of survey respondents were female (31,74,75).…”
Section: Limitationsmentioning
confidence: 99%
“…In Canada, Agyapong et al (138) launched a daily supportive SMS text messaging program "Text4Hope" to test the changes in the level of stress, anxiety, and depression of subscribers after 6 weeks of exposure to the daily supportive SMS text messages during the COVID-19 pandemic. The results indicated that at the 6-week and 3month time points, there was a statistically significant fall in mean score on the 10-item Perceived Stress Scale (PSS-10), the 9-item Patient Health Questionnaire and the 7-item Generalized Anxiety Disorder-7 (GAD-7) (138)(139)(140). Similar results could also be found in another study carried out by Agyapong et al (141).…”
Section: Before and During Disaster: Anticipating And Preparing For Disasterssupporting
confidence: 81%
“…Agyapong et al (139,140) This study describes the changes in the stress, anxiety, and depression levels of subscribers to the Text4Hope program after 3rd month of exposure to daily supportive SMS text messages.…”
Section: References Study Aims Methods Main Findingsmentioning
confidence: 99%
“…In another study, adequacy of living space, housing stability and housing satisfaction were significantly associated with a high prevalence of depression [ 72 ]. This reaffirms that housing is a key social determinant of mental health during the COVID-19 pandemic [ 73 ]. This notwithstanding, housing status did not independently predict depression in this study when other factors were controlled for in the regression model.…”
Section: Discussionsupporting
confidence: 67%